1996
DOI: 10.1089/mdr.1996.2.377
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitous Presence of amecAHomologue in Natural Isolates ofStaphylococcus sciuri

Abstract: In an effort to explore the origin and/or reservoirs of the genetic determinant(s) of methicillin resistance in Staphylococcus aureus, we examined over 200 strains representing 13 different species within the genus Staphylococcus for the presence of the mecA gene, using a DNA probe internal to this gene prepared from a methicillin-resistant strain of S. aureus. Occasional mecA- positive isolates were detected among several staphylococcal species. On the other hand, each one of the 134 isolates of Staphylococcu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
140
0
4

Year Published

1998
1998
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(147 citation statements)
references
References 30 publications
3
140
0
4
Order By: Relevance
“…Polyvalent scaffolding by glycopolymers (glycolipids and glycoproteins) is a known mechanism for organizing proteins in a variety of biological processes (38,39). Whereas there are no genes of high homology to tarS in Staphylococcus sciuri, the organism from which PBP2a was speculated to derive (40,41), all deposited S. aureus strain sequences in the National Center for Biotechnology Information contain tarS. It is possible that PBP2a may exploit β-OGlcNAcylated WTAs by binding to them directly or by interacting with other cellular factors that are scaffolded by these polymers.…”
Section: Discussionmentioning
confidence: 99%
“…Polyvalent scaffolding by glycopolymers (glycolipids and glycoproteins) is a known mechanism for organizing proteins in a variety of biological processes (38,39). Whereas there are no genes of high homology to tarS in Staphylococcus sciuri, the organism from which PBP2a was speculated to derive (40,41), all deposited S. aureus strain sequences in the National Center for Biotechnology Information contain tarS. It is possible that PBP2a may exploit β-OGlcNAcylated WTAs by binding to them directly or by interacting with other cellular factors that are scaffolded by these polymers.…”
Section: Discussionmentioning
confidence: 99%
“…aureus (MSSA) homologue exists (Archer and Neimeyer, 1994) it has been suggested that it was transferred horizontally from a coagulase-negative staphylococcus (CoNS) such as S. sciuri (Couto et al, 1996;Couto et al, 2003). The conjugative transposon containing tetM (tetracycline resistance) has been suggested to pass between Clostridia and staphylococci (Ito et al, 2003), and empirical support for the movement of mobile elements between staphylococci and other low GC gram negative bacteria (Gill et al, 2005), and the potential transfer of vanA (vancomycin resistance) from Enterococcus faecalis to S. aureus (Weigel et al, 2003) lends weight to the possibility of a common gene pool available to many bacterial species (Hanssen et al, 2004).…”
Section: Mrsa In the Non-clinical Environment A Methicillin Resismentioning
confidence: 99%
“…The proportion of S. hominis in the Staphylococcus community is often higher on the glabrous skin of the arms and legs than on other body regions. Strains of S. hominis colonize the skin of a person for relatively short periods of time, usually several weeks to several months, compared to many of the strains of the predominant species Staphylococcus epidermidis that persist for one to several years (Kloos, 1986b;Kloos et al, 1992 1971 1972 1971 1971 1972 1971 1972 1971 1973 1981 198 1 1984 1984 1984 1984 1985 1985 1985 1985 1985 1985 1985 1985 1987 1987 1987 1987 1987 1992 Unknown Unknown Unknown Unknown 1992-1 993 1992-1 993 1992-1 993 1992-1 993 1992-1993 1991 1989 1992-1993 1992-1993 1992-1993 1992-1 993 1992-1 993 1992-1 993 1992-1993 1992-1 993 1992-1 993 1992-1993 1992-1 993 1992-1993 19921992Unknown 1994199619961996 Unknown 1992-1 993…”
Section: Introductionmentioning
confidence: 99%